Unfinished tales of Numenor and Middle-earth - Tolkien, J. R. R. 1892-1973 (HarperCollins, 1980)
Of Tuor and his coming to Gondolin -- Narn i hin Hurin -- A description of the island of Numenor --Aldarion and Erendis -- The line of Elros : Kings of Numenor -- The history of Galadriel and Celeborn --The disaster of the Gladden Fields -- Cirion and Eorl and the friendship of Gondor and Rohan -- The quest of Erebor -- The hunt for the Ring -- The battles of the Fords of Isen -- The Drúedain -- The Istari -- The Palantiri